FAKTOR-FAKTOR YANG MEMPENGARUHI LUASNYA PENGUNGKAPAN LAPORAN KEUANGAN PERUSAHAAN (Studi pada perusahaan Indeks Kompas 100 periode 2012-2014) - Suhailah Amatullah; Afrizal; Junaidi (Magister Ilmu Akuntansi Universitas Jambi, 2016)
This study aimed to analyze the factors that affect the extent of the company's financial statement disclosures . Factors tested were public ownership , company size , profitability , the number of commissioners, the proportion of independent directors and the number of audit committee members.The sampling technique used was purposive sampling method on the company compass 100 index in the Indonesia Stock Exchange 2012-2014 . Sample consisted of 132 company financial statements , there are 73 items to measure broad disclosure of financial statement disclosures .The results showed a positive influence of independent variables which covers all the variables.However, the significant effect is the probability, proportion of independent commissioners and the number of the audit committee